Reorder the terms:
a(b + x) + -1c = d
(b * a + x * a) + -1c = d
(ab + ax) + -1c = d
Solving
ab + ax + -1c = d
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Add 'c' to each side of the equation.
ab + ax + -1c + c = c + d
Combine like terms: -1c + c = 0
ab + ax + 0 = c + d
ab + ax = c + d
Reorder the terms:
ab + ax + -1c + -1d = c + -1c + d + -1d
Combine like terms: c + -1c = 0
ab + ax + -1c + -1d = 0 + d + -1d
ab + ax + -1c + -1d = d + -1d
Combine like terms: d + -1d = 0
ab + ax + -1c + -1d = 0
There is no solution to this equation.